A four-terminal perovskite-crystalline silicon tandem photovoltaic module and a method of manufacturing the same
Patent Information
- Application Number
- CN202611147369.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-30
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2046-07-30
AI Technical Summary
[0007]本发明所要解决的技术问题在于,提供一种四端子钙钛矿-晶硅叠层光伏组件及其制备方法,以期同时解决水氧横向扩散、CTE失配脱层与边缘湿漏电三个问题,在四端子钙钛矿-晶硅叠层光伏组件的顶、底电池之间引入一层蜂窝阻水层,利用复合阻水网格将原本连续整面的光学耦合胶分割为若干个相互独立的封闭微区,并在复合阻水网格与光学耦合胶之间原位构筑IPN(互穿聚合物网络)自锁界面、设计刚-柔模量突变的应力双陷阱,从而把面内“全域连通”的失效通道转化为“逐区隔断、受控释放”的可靠结构,在保持4T叠层组件光学、电学性能的前提下,显著提升其在极端环境下的长期稳定性
1、分区锁水、局部失效阻断:水氧侵入被限制于单一封闭微区内,避免组件大面积连锁失效,显著降低边缘湿漏电风险。
Smart Images

Figure CN122662410B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of perovskite-crystalline silicon tandem photovoltaic modules, and specifically relates to a four-terminal perovskite-crystalline silicon tandem photovoltaic module and its preparation method. Background Technology
[0002] Perovskite-crystalline silicon tandem solar cells, by complementing the wide-bandgap perovskite top cell with the narrow-bandgap crystalline silicon bottom cell in terms of spectrum, can break through the theoretical efficiency limit of monocrystalline silicon cells and are one of the important technical routes for achieving high efficiency and low cost of electricity in the current photovoltaic industry. According to the electrical connection method of the top and bottom cells, tandem cells can be divided into two-terminal (2T) monolithic integrated structures and four-terminal (4T) mechanically stacked structures. In the 4T structure, the top and bottom cells have independent electrodes and operate independently, while they are mechanically stacked and optically coupled through an optical coupling medium (optical coupling adhesive layer).
[0003] Perovskite materials are extremely sensitive to moisture and oxygen, and they are prone to decomposition in humid and hot environments (e.g., organic-inorganic hybrid perovskites decompose into lead iodide, methylamine halides, etc. under the influence of moisture), leading to irreversible degradation of module performance. To ensure the outdoor service life of modules (typically required to be over 25 years), tandem modules must undergo rigorous encapsulation to prevent water and oxygen intrusion, and pass accelerated aging tests such as dual 85 damp heat (DH85℃, RH85%, where DH is an abbreviation for Damp Heat and RH is an abbreviation for Relative Humidity) and temperature cycling (TC, −40℃↔85℃) as specified by standards such as IEC61215 and IEC61730. Existing 4T tandem modules generally follow the mature encapsulation paradigm of crystalline silicon modules, that is, adopting a full-surface laminated structure of "front cover / encapsulation film / cell / encapsulation film / backsheet", and introducing an additional layer of continuous, full-surface optical coupling adhesive in the middle to bond and couple the top and bottom cells. This paradigm works well on single-crystal silicon modules, but when directly applied to 4T multilayer modules containing perovskite, a series of insurmountable reliability problems are exposed due to factors such as the high moisture and oxygen sensitivity of perovskite, the thermo-mechanical mismatch of top and bottom materials, and the complex leads of the four terminals.
[0004] The existing full-surface lamination and encapsulation structure of 4T stacked modules mainly has the following three problems: 1. Lateral diffusion of water and oxygen leads to large-area cascading failure: A continuous, full-surface optical coupling adhesive layer exists between the top and bottom cells of a 4T tandem module. This optical coupling adhesive layer is interconnected in-plane. Once the seals at the module edges (such as edge sealant or lamination boundaries) experience localized damage or aging failure, external moisture will rapidly diffuse laterally along the in-plane direction through this continuous optical coupling adhesive layer and the interfaces between layers, acting as a "high-speed channel." Because the diffusion channel connects the entire module, localized water and oxygen intrusion will quickly affect a large area of the perovskite top cell, triggering a cascading decomposition of the perovskite and further accelerating the corrosion of the metallized grid lines of the crystalline silicon cells, ultimately resulting in a single point of damage leading to complete failure.
[0005] 2. Thermal Expansion Coefficient (CTE) Mismatch Leading to Interfacial Physical Delamination: Perovskite top cells are typically based on glass or flexible polymer substrates, while crystalline silicon bottom cells are made of monocrystalline silicon; their CTEs differ significantly. During temperature cycling tests (e.g., −40℃ to 85℃), the top and bottom cells undergo varying degrees of thermal expansion and contraction with temperature changes, accumulating alternating interfacial shear stress at the optical coupling adhesive interface between them. The continuous, uniform optical coupling adhesive is insufficient to effectively release this stress. Over long-term cycling, this accumulated interfacial shear stress eventually leads to delamination and air gaps between the optical coupling adhesive layer and the cell interface, causing deterioration of the optical coupling adhesive and power decay, and in severe cases, module failure.
[0006] 3. Edge leakage due to moisture in the complex lead area of the four-terminal module: The 4T tandem module structure requires four electrode terminals to be independently led out from the top and bottom cells, with their leads and busbar structures densely interwoven at the edge of the module. Once moisture enters the edge lead area along the aforementioned lateral channels, it will form ion-conducting channels between the dense leads, causing edge leakage (electrochemical corrosion, increased leakage current). This not only causes power loss and safety hazards, but also further catalyzes the degradation of perovskite and corrosion of metal electrodes, forming a vicious cycle. Summary of the Invention
[0007] The technical problem to be solved by this invention is to provide a four-terminal perovskite-crystalline silicon tandem photovoltaic module and its preparation method, in order to simultaneously solve three problems: lateral diffusion of water and oxygen, CTE mismatch delamination, and edge wet leakage. A honeycomb water-blocking layer is introduced between the top and bottom cells of the four-terminal perovskite-crystalline silicon tandem photovoltaic module. The original continuous optical coupling adhesive is divided into several independent closed micro-regions by using a composite water-blocking mesh. An IPN (interpenetrating polymer network) self-locking interface is constructed in situ between the composite water-blocking mesh and the optical coupling adhesive, and a stress double trap with a sudden change in rigid-flexible modulus is designed. This transforms the in-plane "fully connected" failure channel into a reliable structure of "regional isolation and controlled release". While maintaining the optical and electrical performance of the 4T tandem module, its long-term stability under extreme environments is significantly improved.
[0008] This invention is implemented as follows: a four-terminal perovskite-crystalline silicon tandem photovoltaic module is provided, comprising a front cover plate, an upper encapsulating film, a perovskite top cell, a crystalline silicon bottom cell, a lower encapsulating film, and a backsheet stacked together. A honeycomb water-blocking layer is provided between the perovskite top cell and the crystalline silicon bottom cell. The honeycomb water-blocking layer includes a composite water-blocking mesh and an optical coupling adhesive. The composite water-blocking mesh divides the entire effective power generation area into multiple isolated closed micro-regions. The optical coupling adhesive fills each closed micro-region. An IPN (Interpenetrating Polymer Network) self-locking interface is provided at the interface between the composite water-blocking mesh and the optical coupling adhesive. The elastic modulus of the composite water-blocking mesh is 5~15MPa, and the elastic modulus of the optical coupling adhesive is 100~200MPa.
[0009] Furthermore, the material used to prepare the composite water-blocking mesh is a photocurable spraying solution. This solution comprises 70-80 parts of a first photocurable resin matrix, 20-30 parts of a flexible diluent monomer, 10-20 parts of a flexible block copolymer, 3-6 parts of a first photoinitiator, 3-5 parts of a hydrophobically modified water-absorbing filler, 0.5-1 part of a lubricant, and an appropriate amount of a first solvent. This results in a final viscosity of 8-15 cP at 25°C and a solid content controlled at 25%-35%. The first photocurable resin matrix is a mixture of aliphatic polyurethane acrylate and acrylate-modified polybutadiene, with a mass mixing ratio of 1:1; the flexible diluent monomer is lauryl acrylate (LA) or isodecyl acrylate (IDA); the flexible block copolymer is a copolymer of polypropylene glycol (PPG) and diacrylate; the first photoinitiator is bis(phosphine oxide) and compounded with thioxanthone, with a mass mixing ratio of 3:1 to 5:1; the hydrophobically modified water-absorbing filler is nanoscale zeolite or organic-inorganic hybrid hygroscopic nanoparticles with a surface treated with organosilane hydrophobicity; the lubricant is a nonionic surfactant; and the first solvent is propylene glycol methyl ether (PM) or dipropylene glycol dimethyl ether (DMM).
[0010] Further, the material used to prepare the composite water-blocking mesh is a photocurable coating solution. This solution comprises 60-70 parts of a second photocurable resin matrix, 15-25 parts of a flexible block copolymer, 10-20 parts of an reactive diluent, 2-4 parts of a second photoinitiator, 3-8 parts of a moisture-absorbing filler, 0.5-1 part of a leveling agent, 0.5-2 parts of a thixotropic agent, and an appropriate amount of a second solvent. The photocurable coating solution has a coating viscosity of 1000-6000 cP at 25°C and a solid content controlled at 20-30%. The second photocurable resin matrix is a mixture of bisphenol A type epoxy acrylate and polybutadiene-modified olefin resin, with a mass mixing ratio of 3:2; the flexible block copolymer is a copolymer of polypropylene glycol (PPG) and diacrylate or a copolymer of polytetrahydrofuran ether (PTMEG) and diacrylate; the reactive diluent is a mixture of isobornyl acrylate (IBOA) and trimethylolpropane triacrylate (TMPTA), with a mass mixing ratio of 3:1 to 5:1; the second photoinitiator is 2-hydroxy-2- A composition of methyl-1-phenyl-1-propanone and diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide (TPO) in a mass ratio of 1:2 to 2:1; a moisture-absorbing filler is nano-sized zeolite with a surface treated with organosilane for hydrophobicity; an auxiliary agent is 0.5 to 1 part of BYK-333 leveling agent, and 0.5 to 2 parts of organobentonite or polyurea compound is used as a thixotropic agent; the second solvent is a mixture of cyclohexanone and propylene glycol methyl ether acetate (PGMEA) in a mass ratio of 1:1.
[0011] Further, the material used to prepare the optical coupling adhesive comprises 40-60 parts of oligomer, 30-50 parts of curing diluent, 2-5 parts of cationic photoinitiator, 1-3 parts of free radical photoinitiator, and 0.1-1 parts of additives; the viscosity of the optical coupling adhesive before curing is 50-500 mPa·s, and the refractive index after curing is 1.50-1.53; wherein, the oligomer is a mixture of bisphenol A type epoxy resin and polyurethane acrylate; the curing diluent is 3-ethyl-3-hydroxymethyloxetane as a cationic curing diluent, combined with isobornyl acrylate (IBOA) as a free radical curing diluent; the cationic photoinitiator is triarylsulfonium salt; the free radical photoinitiator is 2-hydroxy-2-methyl-1-phenyl-1-propanone; the additives are γ-glycidyl etheroxypropyltrimethoxysilane (KH-560) silane coupling agent and BYK-307 defoamer.
[0012] Furthermore, the shape of the closed micro-region is any one of rectangle, rhombus, regular hexagon or other polygon, and the distance between opposite sides of the closed micro-region is 5~30mm.
[0013] Furthermore, the height of the honeycomb water-blocking layer is 20~50μm, and the wall thickness of the composite water-blocking grid is 120~150μm.
[0014] This invention is implemented as follows, and also provides a method for preparing a four-terminal perovskite-crystalline silicon tandem photovoltaic module as described above, the preparation method comprising the following steps: Step 1: Pre-fabricate perovskite top cells and crystalline silicon bottom cells separately; Step 2: Using inkjet printing combined with a mask, a pre-prepared photocurable spraying solution is deposited on the upper surface of the crystalline silicon bottom cell according to a preset pattern. Then, pre-curing is performed to set the shape, resulting in a composite water-blocking mesh with multiple closed micro-regions. Step 3: Quantitatively fill each closed micro-area with optical coupling adhesive, and use a UV-LED surface light source to expose the composite water-blocking grid and optical coupling adhesive from above, so that a free radical copolymerization reaction is initiated at the interface between the composite water-blocking grid and the optical coupling adhesive, forming an IPN self-locking interface in situ, and obtaining a honeycomb water-blocking layer. Step 4: Sequentially stack the backsheet, lower encapsulation film, crystalline silicon bottom cell with honeycomb water-blocking layer on the upper surface, perovskite top cell, upper encapsulation film, and front cover plate together, and place the whole assembly into a laminator for lamination to complete the fabrication of the four-terminal perovskite-crystalline silicon tandem photovoltaic module.
[0015] Further, in step two, the photocurable spraying solution is prepared in advance using the following method: at room temperature, the first photocurable resin matrix, flexible diluent monomer, flexible block copolymer, lubricant and an appropriate amount of the first solvent are mixed evenly, the first photoinitiator is added under light-protected conditions, and the mixture is stirred until completely dissolved. The hydrophobic modified water-absorbing filler is slowly added and ultrasonically dispersed to ensure that there is no agglomeration in the mixed solution. Finally, the solution is filtered using a PTFE filter membrane, and the filtered photocurable spraying solution is stored in a light-protected ink can for later use.
[0016] This invention is implemented as follows, and also provides a method for preparing a four-terminal perovskite-crystalline silicon tandem photovoltaic module as described above, the preparation method comprising the following steps: Step 1: Pre-fabricate perovskite top cells and crystalline silicon bottom cells separately; Step 2: Using slit extrusion coating combined with a mask, the pre-prepared curing coating solution is deposited on the upper surface of the crystalline silicon bottom cell according to the preset pattern, and then pre-cured to set the shape, resulting in a composite water-blocking mesh with multiple closed micro-regions. Step 3: Quantitatively fill each closed micro-area with optical coupling adhesive, and use a UV-LED surface light source to expose the composite water-blocking grid and optical coupling adhesive from above, so that a free radical copolymerization reaction is initiated at the interface between the composite water-blocking grid and the optical coupling adhesive, forming an IPN self-locking interface in situ, and obtaining a honeycomb water-blocking layer. Step 4: Sequentially stack the backsheet, lower encapsulation film, crystalline silicon bottom cell with honeycomb water-blocking layer on the upper surface, perovskite top cell, upper encapsulation film, and front cover plate together, and place the whole assembly into a laminator for lamination to complete the fabrication of the four-terminal perovskite-crystalline silicon tandem photovoltaic module.
[0017] Further, in step 2, the photocurable spraying solution is prepared in advance using the following method: the second photocurable resin matrix, flexible block copolymer, and reactive diluent are dissolved in the second solvent and heated and stirred in a 50°C water bath until completely dissolved; after cooling the obtained solution to room temperature, the second photoinitiator, leveling agent, and thixotropic agent are added under light-protected conditions and stirred for 30 minutes; then the hygroscopic filler is slowly added and dispersed at high speed for 45 minutes; the solution is filtered and degassed using a 10~20μm filter membrane, and the obtained photocurable spraying solution is allowed to stand and mature for 12 hours before use.
[0018] Compared with the prior art, the four-terminal perovskite-crystalline silicon tandem photovoltaic module and its preparation method of the present invention have the following characteristics: 1. Zoned water locking and local failure prevention: Water and oxygen intrusion is confined to a single closed micro-zone, avoiding large-area chain failure of components and significantly reducing the risk of edge wet leakage.
[0019] 2. Thermal stress release and delamination suppression: The modulus gradient between the composite water-blocking mesh and the optical coupling adhesive, together with the stress release network formed by the IPN self-locking interface, actively absorbs the CTE mismatch shear force, and the delamination area ratio of the interface decreases significantly after temperature cycling.
[0020] 3. Near-zero additional optical loss: The composite water-blocking grid falls within the optical dead zone projection of the perovskite top cell laser scribing and basically coincides with the metal grid lines on the upper surface of the crystalline silicon bottom cell in the vertical direction, hardly blocking the effective power generation area and having minimal impact on the initial power of the 4T tandem photovoltaic module.
[0021] 4. Interface self-locking and heterogeneous compatibility: The IPN self-locking interface integrates the heterogeneous mesh with the filler adhesive at the molecular level, solving the problem of interface tearing in heterogeneous colloids.
[0022] 5. Process compatibility and mass production capability: Deposition, filling, laser crosslinking, and lamination processes can all be integrated into existing component production lines. Attached Figure Description
[0023] Figure 1 This is a schematic diagram of the internal structure of the four-terminal perovskite-crystalline silicon tandem photovoltaic module of the present invention; Figure 2 for Figure 1 Top view of the honeycomb water-blocking layer; Figure 3 The graph shows the normalized power attenuation curves at DH1000h for the four-terminal perovskite-crystalline silicon tandem photovoltaic modules prepared in Example 1 and Comparative Example 1 of this invention. Figure 4 A comparison chart of the TC200 temperature cycling delamination rates of the four-terminal perovskite-crystalline silicon tandem photovoltaic modules prepared in Example 2 and Comparative Example 2 of the present invention. Figure 5The image shows a comparison of the TC200 edge leakage current of the four-terminal perovskite-crystalline silicon tandem photovoltaic modules prepared in Example 2 and Comparative Example 2 of this invention. Figure 6 This is a comparison diagram showing the lateral diffusion range of water vapor after partial damage to the four-terminal perovskite-crystalline silicon tandem photovoltaic modules prepared in Example 3 and Comparative Example 3 of the present invention.
[0024] The labels in each diagram are as follows: 1. Front cover plate; 2. Upper encapsulation film; 3. Perovskite top cell; 4. Composite water-blocking mesh; 5. Optical coupling adhesive; 6. Crystalline silicon bottom cell; 7. Honeycomb water-blocking layer; 8. Lower encapsulation film; 9. Backsheet; 10. IPN self-locking interface; 11. Module edge encapsulation boundary; 12. Effective power generation area; 13. Enclosed micro-area. Detailed Implementation
[0025] To make the technical problems to be solved, the technical solutions, and the beneficial effects of the present invention clearer, the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative of the present invention and are not intended to limit the present invention.
[0026] Please refer to the following at the same time Figure 1 as well as Figure 2 As shown, a preferred embodiment of the four-terminal perovskite-crystalline silicon tandem photovoltaic module of the present invention includes a front cover plate 1, an upper encapsulation film 2, a perovskite top cell 3, a crystalline silicon bottom cell 6, a lower encapsulation film 8, and a backplate 9 stacked together, with a honeycomb water-blocking layer 7 disposed between the perovskite top cell 3 and the crystalline silicon bottom cell 6.
[0027] The honeycomb water-blocking layer 7 includes a composite water-blocking mesh 4 and an optical coupling adhesive 5. The composite water-blocking mesh 4 physically divides the entire effective power generation area 12 into multiple isolated and independent closed micro-regions 13, and the optical coupling adhesive 5 fills each closed micro-region 13. An IPN (Interpenetrating Polymer Network) self-locking interface 10 is provided at the interface between the composite water-blocking mesh 4 and the optical coupling adhesive 5. The elastic modulus of the composite water-blocking mesh 4 is 5~15MPa, and the elastic modulus of the optical coupling adhesive 5 is 100~200MPa. Figure 2 As shown, the effective power generation area 12 is located within the inner region of the module edge encapsulation boundary 11 of the four-terminal perovskite-crystalline silicon tandem photovoltaic module.
[0028] As an example, the material used to prepare the composite water-blocking mesh 4 is a photocurable spraying solution. The photocurable spraying solution consists of 70-80 parts of a first photocurable resin matrix, 20-30 parts of a flexible diluent monomer, 10-20 parts of a flexible block copolymer, 3-6 parts of a first photoinitiator, 3-5 parts of a hydrophobic modified water-absorbing filler, 0.5-1 parts of a lubricant, and an appropriate amount of a first solvent. The final viscosity of the photocurable spraying solution is 8-15 cP at 25°C, and the solid content is controlled at 25-35%.
[0029] Specifically, the first photocurable resin matrix is a mixture of low-viscosity aliphatic polyurethane acrylate (such as Sartamomer CN9001) and acrylate-modified polybutadiene (such as Ricacryl 3801), with a mass mixing ratio of 1:1, to provide basic mechanical strength and flexibility. The flexible diluent monomer is a high-solubility, low-viscosity lauryl acrylate (LA) or isodecyl acrylate (IDA) as an reactive diluent to adjust viscosity. The flexible block copolymer is a copolymer of polypropylene glycol (PPG) and diacrylate, with a molecular weight of approximately 2000 Da, serving as the flexible segment. The first photoinitiator is a bis(acylphosphine) oxide (such as photoinitiator 819) with higher response efficiency to long-wavelength UV light, and is compounded with a small amount of thioxanthone (such as ITX) to improve deep curing ability; the mass mixing ratio of the two is 3:1 to 5:1, preferably 4:1. The hydrophobically modified absorbent filler is a nano-sized zeolite (average particle size D50≤200nm) with a surface treated with an organosilane for hydrophobicity or an organic-inorganic hybrid hygroscopic nanoparticle (such as sodium polyacrylate-grafted silica). The lubricant is a nonionic surfactant as a wetting agent (such as BYK-345). The primary solvent is a highly volatile, low-surface-tension single solvent, such as propylene glycol methyl ether (PM) or dipropylene glycol dimethyl ether (DMM).
[0030] In another embodiment, the material used to prepare the composite water-blocking mesh 4 is a photocurable coating solution. The photocurable coating solution consists of 60-70 parts of a second photocurable resin matrix, 15-25 parts of a flexible block copolymer, 10-20 parts of an reactive diluent, 2-4 parts of a second photoinitiator, 3-8 parts of a moisture-absorbing filler, 0.5-1 parts of a leveling agent, 0.5-2 parts of a thixotropic agent, and an appropriate amount of a second solvent. The coating viscosity of the photocurable coating solution is 1000-6000 cP at 25°C, and the solid content is controlled at 20-30%.
[0031] Specifically, the second photocurable resin matrix is a mixture of bisphenol A type epoxy acrylate (such as CN104) and polybutadiene-modified olefin resin (such as CN307), with a mass mixing ratio of 3:2. The flexible block copolymer is a copolymer of polypropylene glycol (PPG) and diacrylate, with a molecular weight of 3000~5000 Da, or a copolymer of polytetrahydrofuran ether (PTMEG) and diacrylate. The reactive diluent is a mixture of isobornyl acrylate (IBOA) and trimethylolpropane triacrylate (TMPTA), with a mass mixing ratio of 3:1 to 5:1, preferably 4:1. The second photoinitiator is a composition of 2-hydroxy-2-methyl-1-phenyl-1-propanone (photoinitiator 1173) and diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide (TPO), with a mass mixing ratio of 1:2 to 2:1, preferably 1:1, used to initiate free radical polymerization under UV irradiation. The hygroscopic filler is nanoscale zeolite (average particle size D50 ≤ 200 nm) with a surface treated with organosilane for hydrophobicity, to avoid the negative impact of conventional molecular sieves on photocuring and storage stability. The leveling agent is BYK-333, and the thixotropic agent is organobentonite (such as BYK Laponite RD) or a polyurea compound (such as BYK-410), which facilitates the construction of a stable thixotropic network at medium viscosity. The second solvent is a mixture of cyclohexanone and propylene glycol methyl ether acetate (PGMEA) at a mass ratio of 1:1.
[0032] The material used to prepare the optical coupling adhesive 5 consists of 40-60 parts of oligomer, 30-50 parts of curing diluent, 2-5 parts of cationic photoinitiator, 1-3 parts of free radical photoinitiator, and 0.1-1 parts of additives. The viscosity of the optical coupling adhesive 5 before curing is 50-500 mPa·s, measured at 25°C using a Brookfield DV2T viscometer (rotor S61). The refractive index after curing is 1.50-1.53, measured at 589 nm wavelength using an Abbe refractometer, matching the glass cover and battery encapsulation materials. The elastic modulus after curing is approximately 100-200 MPa, measured by dynamic mechanical analysis (DMA).
[0033] Specifically, the oligomer is a mixture of bisphenol A type epoxy resin (such as EPON 828) and polyurethane acrylate (such as EBECRYL 4858), providing cationic and free radical curing crosslinking networks, respectively. The curing diluent is 3-ethyl-3-hydroxymethyloxetane as the cationic curing diluent, combined with isobornyl acrylate (IBOA) as the free radical curing diluent. The cationic photoinitiator is a triarylsulfonium salt (such as Chivacure 1176). The free radical photoinitiator is 2-hydroxy-2-methyl-1-phenyl-1-propanone (photoinitiator 1173). Additives include γ-glycidyl etheroxypropyltrimethoxysilane (KH-560) silane coupling agent to enhance adhesion to the glass substrate and grid wall, and BYK-307 defoamer.
[0034] The shape of the closed micro-region 13 is any one of rectangle, rhombus, regular hexagon or other polygon, and the distance between opposite sides of the closed micro-region 13 is 5~30mm.
[0035] The height of the honeycomb water-blocking layer 7 is 20~50μm, and the wall thickness of the composite water-blocking grid 4 is 120~150μm (less than or equal to the width of the metal grid line).
[0036] Metal grid lines are provided on the upper surface of the crystalline silicon bottom cell 6. The composite water-blocking grid 4 is basically overlapped with the metal grid lines in the vertical direction, and the wall thickness of the composite water-blocking grid 4 is not greater than the width of the metal grid lines.
[0037] Please refer to again Figure 1 As shown, the present invention also discloses a method for preparing a four-terminal perovskite-crystalline silicon tandem photovoltaic module as described above, the preparation method comprising the following steps: Step 1: Pre-fabricate the perovskite top cell 3 and the crystalline silicon bottom cell 6 separately.
[0038] Step 2: Using inkjet printing combined with a mask, the pre-prepared photocurable spray solution is deposited on the upper surface of the crystalline silicon bottom cell 6 directly above the metal grid lines according to the preset pattern. Then, pre-curing (pre-crosslinking) is performed to shape it, resulting in a composite water-blocking grid 4 with multiple closed micro-regions 13.
[0039] Step 3: Quantitatively fill each closed micro-region 13 with optical coupling adhesive 5, ensuring it fills each closed micro-region 13 and is in close contact with the sidewall of the composite water-blocking mesh 4. Vacuum assistance can be used to remove air bubbles. A 365nm UV-LED surface light source is used to expose the composite water-blocking mesh 4 and optical coupling adhesive 5 from above, causing a free radical copolymerization reaction to be initiated at the interface between the composite water-blocking mesh 4 and the optical coupling adhesive 5, forming an in-situ 5~10μm thick IPN self-locking interface 10, resulting in a honeycomb water-blocking layer 7.
[0040] Step 4: Stack the backsheet 9, the lower encapsulation film 8, the crystalline silicon bottom cell 6 with the honeycomb water-blocking layer 7 already prepared on the upper surface, the perovskite top cell 3, the upper encapsulation film 2, and the front cover plate 1 together in sequence, and put the whole assembly into a laminator for lamination to complete the preparation of the four-terminal perovskite-crystalline silicon tandem photovoltaic module.
[0041] In step two, the photocurable spraying solution is prepared in advance using the following method: at room temperature, the first photocurable resin matrix, flexible diluent monomer, flexible block copolymer, lubricant and appropriate amount of first solvent are mixed evenly, the first photoinitiator is added under light-protected conditions, and the mixture is stirred until completely dissolved. The hydrophobic modified water-absorbing filler is slowly added, and the mixture is ultrasonically dispersed for 30 minutes to ensure that there is no agglomeration in the mixed solution. Finally, the solution is filtered using a PTFE filter membrane with a pore size ≤0.45μm, and the filtered photocurable spraying solution is stored in a light-protected ink can for later use.
[0042] Please refer to again Figure 1 As shown, the present invention also discloses another method for preparing a four-terminal perovskite-crystalline silicon tandem photovoltaic module as described above, the preparation method comprising the following steps: Step 1: Pre-fabricate the perovskite top cell 3 and the crystalline silicon bottom cell 6 respectively.
[0043] Step 2: Using a slit extrusion coating combined with a mask, the pre-prepared curing coating solution is deposited on the upper surface of the crystalline silicon bottom cell 6 directly above the metal grid lines according to a preset pattern. Then, pre-curing (pre-crosslinking) is performed to shape the composite water-blocking grid 4 with multiple closed micro-regions 13.
[0044] Step 3: Quantitatively fill each closed micro-region 13 with optical coupling adhesive 5, ensuring that it fills each closed micro-region 13 and is in close contact with the sidewall of the composite water-blocking mesh 4; vacuum assistance can be used to remove air bubbles, and a 365nm UV-LED surface light source is used to expose the composite water-blocking mesh 4 and optical coupling adhesive 5 from above, so that a free radical copolymerization reaction is initiated at the interface between the composite water-blocking mesh 4 and the optical coupling adhesive 5, forming an in-situ 5~10μm thick IPN self-locking interface 10, resulting in a honeycomb water-blocking layer 7.
[0045] Step 4: Stack the backsheet 9, the lower encapsulation film 8, the crystalline silicon bottom cell 6 with the honeycomb water-blocking layer 7 already prepared on the upper surface, the perovskite top cell 3, the upper encapsulation film 2, and the front cover plate 1 together in sequence, and put the whole assembly into a laminator for lamination to complete the preparation of the four-terminal perovskite-crystalline silicon tandem photovoltaic module.
[0046] In step 2, the photocurable spraying solution is prepared in advance using the following method: the second photocurable resin matrix, flexible block copolymer, and reactive diluent are dissolved in the second solvent and heated and stirred in a 50°C water bath until completely dissolved; after cooling the obtained solution to room temperature, the second photoinitiator, leveling agent, and thixotropic agent are added under light-protected conditions and stirred for 30 minutes; then the hygroscopic filler is slowly added and dispersed at high speed (1000~1500 rpm) for 45 minutes; the solution is filtered and degassed using a 10~20μm filter membrane, and the obtained photocurable spraying solution is allowed to stand and mature for 12 hours before use.
[0047] The four-terminal perovskite-crystalline silicon tandem photovoltaic module and its preparation method of the present invention also have the following characteristics: 1. Local failure prevention (zoned water locking) The honeycomb-shaped composite water-blocking mesh 4 divides the continuous optical coupling adhesive 5 into several closed micro-regions 13, thus blocking the originally interconnected lateral diffusion channels of water and oxygen within the surface. When the encapsulation of the photovoltaic module is damaged at the edge or in a certain area, the intruding water and oxygen can only diffuse within the single closed micro-region 13 it is currently in. Upon reaching the sidewall of the composite water-blocking mesh 4, it is blocked and cannot spread laterally to adjacent closed micro-regions 13 or the surrounding area. This achieves local failure blocking (regional water locking), fundamentally avoiding "one-site damage, whole-system failure," and limiting the impact of edge wet leakage to a single closed micro-region 13, greatly reducing the risk of edge wet leakage.
[0048] 2. Precision geometric matching achieves near-zero additional optical loss This invention utilizes the inherent metal grid lines (including main grids and / or fine grids, typically 30-500 μm wide) on the surface of the crystalline silicon bottom cell 6 as the accommodating space for the composite water-blocking grid 4. Since the metal grid lines themselves are opaque and do not participate in power generation, after the composite water-blocking grid 4 is precisely deposited directly above the metal grid lines, it is completely blocked by the metal grid lines in the vertical direction, thus achieving zero additional optical loss at the photovoltaic module level. The composite water-blocking grid 4 is precisely deposited within the orthogonal projection range of the metal grid lines using high-precision UV inkjet printing or slot-die coating combined with a mask. The width of the composite water-blocking grid 4 is strictly controlled to be 120-150 μm, less than or equal to the width of the metal grid lines, and its height is controlled to be 20-50 μm. Because the composite water-blocking grid 4 falls within the originally non-power-generating dead zone projection, it almost does not additionally block the effective power generation area 12, thus achieving near-zero additional optical loss. It should be noted that even if the composite water-blocking grid 4 falls into the power generation area due to a mismatch in shape with the metal grid lines of the crystalline silicon bottom cell 6, its impact remains limited. Firstly, the metal grid lines themselves are opaque, and the crystalline silicon bottom cell 6 design implicitly accepts a 3-5% light-blocking loss from the metal grid lines. Secondly, the width of the composite water-blocking grid 4 (120-150 μm) is comparable to the width of the metal grid lines, resulting in a light-blocking area ratio of only about 1.2-1.6%. Furthermore, the top and bottom cells are decoupled under the 4T structure, eliminating the risk of reverse bias hotspots, and the measured temperature rise is <3℃. Therefore, the composite water-blocking grid 4 can be considered an "acceptable light-blocking structure" similar to the metal grid lines. This solution does not require shape matching and offers high process tolerance.
[0049] 3. In-situ crosslinking and interfacial self-locking of heterogeneous materials (IPN self-locking interface) An IPN self-locking interface 10 with a thickness of about 5~10μm is formed in situ at the interface between the composite water-blocking mesh 4 and the optical coupling adhesive 5. On the one hand, the IPN self-locking interface 10 forms abrupt and dense water-blocking boundary in a physical sense, which further enhances the water-locking effect on the closed micro-region 13; on the other hand, it "locks" the composite water-blocking mesh 4 and the optical coupling adhesive 5 together at the molecular level, which solves the problem that the two heterogeneous colloids are prone to tearing and peeling at the interface due to CTE mismatch.
[0050] 4. Edge stress double trap (modulus gradient actively absorbs shear force) This invention abandons the difficult-to-control rheological gradient scheme and instead uses chemical structure design to construct a stress-relieving network: long-chain siloxane blocks are introduced into the composite water-blocking mesh 4, making its post-curing elastic modulus (approximately 10 MPa) much lower than that of the intermediate optical coupling adhesive 5 (approximately 150 MPa). When the tandem photovoltaic module deforms due to thermal shock, the rigid optical coupling adhesive 5 transfers the interfacial shear force to the adjacent, highly elastic composite water-blocking mesh 4. The composite water-blocking mesh 4 acts as a strain buffer, actively absorbing and dissipating the shear stress generated by CTE mismatch through its own elastic deformation, thereby suppressing delamination at the top and bottom cell interfaces. The interface with the abrupt change in modulus between the rigid (optical coupling adhesive 5) and flexible (composite water-blocking mesh 4) forms a pair of stress double traps on both sides of the composite water-blocking mesh 4, causing the stress to be absorbed at the composite water-blocking mesh 4 rather than accumulating at the cell / adhesive interface.
[0051] Please refer to again Figure 1 As shown, the following specific embodiments further illustrate the four-terminal perovskite-crystalline silicon tandem photovoltaic module of the present invention and its preparation method.
[0052] Example 1: Stability of DH1000h under damp heat (85) The first embodiment of the method for preparing a four-terminal perovskite-crystalline silicon tandem photovoltaic module of the present invention includes the following steps: Step 11: Pre-fabricate the perovskite top cell 3 and the crystalline silicon bottom cell 6 separately. The substrate of the perovskite top cell 3 is glass, and the width of the metal grid lines on the upper surface of the crystalline silicon bottom cell 6 is 150 μm.
[0053] Step 12: Using a slit extrusion coating combined with a mask, the pre-prepared curing coating solution is deposited onto the upper surface of the crystalline silicon bottom cell 6 directly above the metal grid lines according to a preset pattern. Pre-curing (pre-crosslinking) is then performed to shape the composite water-blocking mesh 4 with multiple closed microregions 13. The mask opening is aligned with the metal grid lines, the coating speed is 15 mm / s, and the wet film thickness is controlled at 40 μm (target dry film thickness 35 μm). After coating, it is pre-baked on a 60°C hot plate for 2 minutes to evaporate the solvent. Subsequently, it is cured using a 365 nm UV-LED in a nitrogen atmosphere at an energy of 800 mJ / cm². The elastic modulus of the cured composite water-blocking mesh 4 is approximately 5 MPa.
[0054] The composite water-blocking mesh 4 is a regular hexagon with a side-to-side distance of approximately 12 mm. The width of the composite water-blocking mesh 4 is 120 μm, and the height is 35 μm.
[0055] In this embodiment, the components of the photocurable coating solution are: 65 parts of a second photocurable resin matrix (a mixture of bisphenol A type epoxy acrylate and polybutadiene modified olefin resin, mass ratio 3:2), 20 parts of a flexible block copolymer (a copolymer of polypropylene glycol and diacrylate, molecular weight 3000~5000 Da), 15 parts of an reactive diluent (a mixture of isoborneol acrylate and trimethylolpropane triacrylate, mass ratio 4:1), and 3 parts of a second photoinitiator (2-hydroxy-2-methyl-1- The composition of phenyl-1-propanone and diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide (mass ratio 1:1), 5.5 parts of hygroscopic filler (nanoscale zeolite with surface hydrophobic treatment by organosilane, D50≤200nm), 0.8 parts of leveling agent (BYK-333), 1 part of thixotropic agent (organo-bentonite), and an appropriate amount of second solvent (a mixed solvent of cyclohexanone and propylene glycol methyl ether acetate, mass ratio 1:1) are adjusted to a coating viscosity of 3500 cP at 25°C, and the solid content is controlled at 25%.
[0056] Step 13: Quantitatively fill each sealed micro-region 13 with optical coupling adhesive 5 with a viscosity of 275 mPa·s, ensuring it fills each micro-region 13 and makes tight contact with the sidewalls of the composite water-blocking mesh 4. The vacuum level is controlled at -0.08 MPa to ensure bubble-free filling. The composite water-blocking mesh 4 and optical coupling adhesive 5 are exposed from above using a 365 nm UV-LED surface light source with a light intensity of 100 mW / cm² for 60 seconds. This initiates a free radical copolymerization reaction at the interface between the composite water-blocking mesh 4 and the optical coupling adhesive 5, forming a 7 μm thick IPN self-locking interface 10 in situ, resulting in the honeycomb water-blocking layer 7. The elastic modulus of the cured optical coupling adhesive 5 is approximately 150 MPa. In this embodiment, the optical coupling adhesive 5 comprises: 40 parts of oligomer (a mixture of bisphenol A epoxy resin and polyurethane acrylate, in a mass ratio of 1:1), 50 parts of curing diluent (a mixture of 3-ethyl-3-hydroxymethyloxetane and isobornyl acrylate, in a mass ratio of 1:1), 5 parts of cationic photoinitiator (triarylthionium salt), 3 parts of free radical photoinitiator (2-hydroxy-2-methyl-1-phenyl-1-propanone), and 1 part of additive (a mixture of γ-glycidyl etheroxypropyltrimethoxysilane and BYK-307 defoamer, in a mass ratio of 1:1).
[0057] Step 14: Sequentially stack the backsheet 9, the lower encapsulating film 8, the crystalline silicon bottom cell 6 with the honeycomb water-blocking layer 7 already prepared on its upper surface, the perovskite top cell 3, the upper encapsulating film 2, and the front cover plate 1 together, and place the entire assembly into a laminator for lamination to complete the fabrication of the four-terminal perovskite-crystalline silicon tandem photovoltaic module. The lamination parameters are: vacuum for 5 minutes, lamination temperature 145℃, pressure -60kPa, and pressure holding for 15 minutes.
[0058] Comparative Example 1 The difference between this comparative example and Example 1 is that the honeycomb water-blocking layer 7 is a continuous optical coupling adhesive layer with a thickness of 35 μm, without the composite water-blocking mesh 4 and without a honeycomb mesh structure. Other structures and preparation steps are the same as in Example 1 and will not be repeated.
[0059] The four-terminal perovskite-crystalline silicon tandem photovoltaic modules prepared in Example 1 and Comparative Example 1 were subjected to comparative performance tests. According to IEC 61215, the four-terminal perovskite-crystalline silicon tandem photovoltaic modules prepared in Example 1 and Comparative Example 1 were placed in the same batch in a dual 85% RH humidity chamber for accelerated aging. The modules were removed at 0h, 100h, 200h, 300h, 500h, 700h, and 1000h, respectively, and the maximum power Pmax was measured and normalized to the initial power.
[0060] Comparison test results as follows Figure 3 As shown. In Comparative Example 1, the tandem photovoltaic module experienced rapid power decay due to the lateral diffusion of water and oxygen along the continuous adhesive layer, leading to the chain decomposition of perovskite. Its power dropped below the 95% criterion line after approximately 300 hours, and the normalized power was only about 48% after 1000 hours. In contrast, the tandem photovoltaic module of Example 1 of this invention benefits from zoned water locking and in-situ water absorption by molecular sieves, confining water and oxygen to a single micro-region. After 1000 hours, the normalized power still remained at approximately 95.3%, meeting the IEC criteria. Figure 3 This indicates that the tandem photovoltaic module of Embodiment 1 of the present invention can reduce the power attenuation of DH1000h from about 52% in Comparative Example 1 to about 4.7%, with an attenuation of no more than 5% (i.e., normalized power ≥ 95%), and achieves an order-of-magnitude improvement in long-term damp heat stability, fully verifying that the honeycomb water-blocking layer 7 has a zoned water-locking effect.
[0061] Example 2: Temperature Cycling (TC200) Anti-Delamination and Anti-Leakage A second embodiment of the method for preparing a four-terminal perovskite-crystalline silicon tandem photovoltaic module of the present invention includes the following steps: Step 21: Pre-fabricate the perovskite top cell 3 and the crystalline silicon bottom cell 6 respectively.
[0062] Step 22: Using a slit extrusion coating combined with a mask, the pre-prepared curing coating solution is deposited in a preset pattern directly above the metal grid lines on the upper surface of the crystalline silicon bottom cell 6. Pre-curing (pre-crosslinking) is then performed to shape the composite water-blocking mesh 4, which has multiple closed microregions 13. The composite water-blocking mesh 4 has a width of 150 μm and a height of 20 μm.
[0063] In this embodiment, the components of the photocurable coating solution are: 60 parts of a second photocurable resin matrix (a mixture of bisphenol A type epoxy acrylate and polybutadiene modified olefin resin, mass ratio 3:2), 25 parts of a flexible block copolymer (a copolymer of polytetrahydrofuran ether and diacrylate), 10 parts of an reactive diluent (a mixture of isoborneol acrylate and trimethylolpropane triacrylate, mass ratio 3:1), and 4 parts of a second photoinitiator (2-hydroxy-2-methyl-1-phenyl) A composition of 1-propanone and diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide (mass ratio 2:1), 3 parts of hygroscopic filler (nanoscale zeolite with surface hydrophobic treatment by organosilane), 0.5 parts of leveling agent (BYK-333), 0.5 parts of thixotropic agent (polyurea compound), and an appropriate amount of second solvent (a mixture of cyclohexanone and propylene glycol methyl ether acetate, mass ratio 1:1) were used to adjust the coating viscosity to 1000 cP at 25°C, with a solid content controlled at 20%. The mask opening was aligned with the metal grid lines, the coating speed was 10 mm / s, and the wet film thickness was controlled at 23 μm (target dry film thickness 35 μm). After coating, the film was pre-baked on a hot plate at 60°C for 1.5 minutes to evaporate the solvent. Subsequently, it was cured using a 365 nm UV-LED in a nitrogen atmosphere at an energy of 700 mJ / cm². The elastic modulus of the cured composite water-blocking mesh 4 was approximately 10 MPa.
[0064] Step 23: Quantitatively fill each sealed micro-region 13 with optical coupling adhesive 5 with a viscosity of 200 mPa·s, ensuring it fills each micro-region 13 and is in close contact with the sidewalls of the composite water-blocking mesh 4. Vacuum assistance can be used to remove air bubbles. A 365 nm UV-LED surface light source is used to expose the composite water-blocking mesh 4 and optical coupling adhesive 5 from above, initiating a free radical copolymerization reaction at the interface between the composite water-blocking mesh 4 and the optical coupling adhesive 5, forming a 5 μm thick IPN self-locking interface 10 in situ, resulting in a honeycomb water-blocking layer 7. The elastic modulus of the cured optical coupling adhesive 5 is approximately 100 MPa. In this embodiment, the optical coupling adhesive 5 comprises: 50 parts of oligomer (a mixture of bisphenol A type epoxy resin and polyurethane acrylate, with a mass ratio of 1.5:1), 40 parts of curing diluent (a mixture of 3-ethyl-3-hydroxymethyloxetane and isobornyl acrylate, with a mass ratio of 1.5:1), 3.5 parts of cationic photoinitiator (triarylthionium salt), 2 parts of free radical photoinitiator (2-hydroxy-2-methyl-1-phenyl-1-propanone), and 0.5 parts of additive (a mixture of γ-glycidyl etheroxypropyltrimethoxysilane and BYK-307 defoamer, with a mass ratio of 1:1).
[0065] Step 24: Stack the backplate 9, the lower encapsulation film 8, the crystalline silicon bottom cell 6 with the honeycomb water-blocking layer 7 already prepared on the upper surface, the perovskite top cell 3, the upper encapsulation film 2, and the front cover plate 1 together in sequence, and put the whole assembly into a laminator for lamination to complete the preparation of the four-terminal perovskite-crystalline silicon tandem photovoltaic module.
[0066] Comparative Example 2 The difference between this comparative example and Example 2 is that the honeycomb water-blocking layer 7 is a continuous optical coupling adhesive layer with a thickness of 35 μm, without the composite water-blocking mesh 4 and without a honeycomb mesh structure. Other structures and preparation steps are the same as in Example 2 and will not be repeated here.
[0067] The four-terminal perovskite-crystalline silicon tandem photovoltaic modules prepared in Example 2 and Comparative Example 2 were subjected to performance comparison tests. According to IEC 61215, the four-terminal perovskite-crystalline silicon tandem photovoltaic modules prepared in Example 2 and Comparative Example 2 were placed in a temperature cycling chamber at −40℃↔85℃ for the same batch. After 0, 50, 100, 150, and 200 cycles, the delamination area ratio at the interface between the top and bottom cells was measured using a scanning ultrasonic microscope (C-SAM). After TC200, the leakage current of the edge lead area of the photovoltaic module under wet bias was measured and compared with the initial state (TC0) and Comparative Example 2.
[0068] Comparison test results as follows Figure 4 and Figure 5 As shown. In Figure 4 In Comparative Example 2, the delamination area ratio of the photovoltaic module interface increased rapidly with the number of cycles, reaching approximately 14.5% at TC200; however, the photovoltaic module of Example 2, due to the active absorption of shear stress by the stress double trap, had a delamination area ratio of only approximately 1.1% at TC200. Figure 5 In Comparative Example 2, after TC200, the edge leakage current increased from approximately 0.8 nA to approximately 38.5 nA (due to water and oxygen intrusion into the edge lead region), while in Example 2 it only increased to approximately 2.1 nA. This verifies the synergistic effect of the IPN self-locking interface and stress double trap structure in suppressing delamination and edge leakage.
[0069] Example 3: Blocking the lateral diffusion of water vapor after localized artificial damage A third embodiment of the method for preparing a four-terminal perovskite-crystalline silicon tandem photovoltaic module of the present invention includes the following steps: Step 31: Pre-fabricate the perovskite top cell 3 and the crystalline silicon bottom cell 6 respectively.
[0070] Step 32: Using a slit extrusion coating combined with a mask, the pre-prepared curing coating solution is deposited on the upper surface of the crystalline silicon bottom cell 6 directly above the metal grid lines according to a preset pattern. Pre-curing (pre-crosslinking) is then performed to shape the surface, resulting in a composite water-blocking mesh 4 with multiple closed microregions 13. The composite water-blocking mesh 4 has a width of 135 μm and a height of 50 μm.
[0071] In this embodiment, the components of the photocurable coating solution are: 70 parts of a second photocurable resin matrix (a mixture of bisphenol A type epoxy acrylate and polybutadiene modified olefin resin, with a mass ratio of 3:2), 15 parts of a flexible block copolymer (a copolymer of polypropylene glycol and diacrylate), 20 parts of an reactive diluent (a mixture of isoborneol acrylate and trimethylolpropane triacrylate, with a mass ratio of 5:1), and 2 parts of a second photoinitiator (2-hydroxy-2-methyl-1-benzene). A composition of 1-propanone and diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide (mass ratio 1:2), 8 parts of hygroscopic filler (nano-scale zeolite with surface hydrophobic treatment by organosilane), 1 part of leveling agent (BYK-333), 2 parts of thixotropic agent (organo-bentonite), and an appropriate amount of a second solvent (a mixture of cyclohexanone and propylene glycol methyl ether acetate, mass ratio 1:1) were used to adjust the coating viscosity to 6000 cP at 25°C, with a solid content controlled at 30%. The mask opening was aligned with the metal grid lines, the coating speed was 10 mm / s, and the wet film thickness was controlled at 23 μm (target dry film thickness 35 μm). After coating, the film was pre-baked on a hot plate at 60°C for 1.5 minutes to evaporate the solvent. Subsequently, it was cured using a 365 nm UV-LED in a nitrogen atmosphere at an energy of 700 mJ / cm². The composite water-blocking mesh 4 had an elastic modulus of approximately 15 MPa after curing.
[0072] Step 33: Quantitatively fill each sealed micro-region 13 with optical coupling adhesive 5 with a viscosity of 500 mPa·s, ensuring it fills each micro-region 13 and forms tight contact with the sidewalls of the composite water-blocking mesh 4. Vacuum assistance can be used to remove air bubbles. A 365 nm UV-LED surface light source is used to expose the composite water-blocking mesh 4 and optical coupling adhesive 5 from above, initiating a free radical copolymerization reaction at the interface between the composite water-blocking mesh 4 and the optical coupling adhesive 5, forming a 10 μm thick IPN self-locking interface 10 in situ, resulting in the honeycomb water-blocking layer 7. The light intensity of the surface light source is 200 mW / cm², and the scanning speed is 2 mm / s. The elastic modulus of the cured optical coupling adhesive 5 is approximately 200 MPa. In this embodiment, the optical coupling adhesive 5 comprises: 60 parts of oligomer (a mixture of bisphenol A epoxy resin and polyurethane acrylate, in a mass ratio of 2:1), 30 parts of curing diluent (a mixture of 3-ethyl-3-hydroxymethyloxetane and isobornyl acrylate, in a mass ratio of 2:1), 2 parts of cationic photoinitiator (triarylthionium salt), 1 part of free radical photoinitiator (2-hydroxy-2-methyl-1-phenyl-1-propanone), and 0.1 parts of additive (a mixture of γ-glycidyl etheroxypropyltrimethoxysilane and BYK-307 defoamer, in a mass ratio of 2:1).
[0073] Step 34: Stack the backsheet 9, the lower encapsulation film 8, the crystalline silicon bottom cell 6 with the honeycomb water-blocking layer 7 already prepared on the upper surface, the perovskite top cell 3, the upper encapsulation film 2, and the front cover plate 1 together in sequence, and put the whole assembly into a laminator for lamination to complete the preparation of the four-terminal perovskite-crystalline silicon tandem photovoltaic module.
[0074] Comparative Example 3 The difference between this comparative example and Example 3 is that the honeycomb water-blocking layer 7 is a continuous optical coupling adhesive layer with a thickness of 35 μm, without the composite water-blocking mesh 4 and without a honeycomb mesh structure. Other structures and preparation steps are the same as in Example 3 and will not be repeated here.
[0075] The four-terminal perovskite-crystalline silicon tandem photovoltaic modules prepared in Example 3 and Comparative Example 3 were subjected to performance comparison tests. The tandem photovoltaic modules of Example 3 and Comparative Example 3 with artificial damage (equivalent damage was created at the same location) were placed in an immersion aging environment at 0h, 24h, 48h, 96h, 168h, 336h, and 504h. Photoluminescence (PL) imaging and C-SAM were used for joint characterization to measure the spread of perovskite degradation and interface failure from the damage point, which was characterized by the equivalent radius.
[0076] Comparison test results as follows Figure 6 As shown. In Figure 6In Comparative Example 3, water and oxygen diffused freely laterally along the continuous interface in the tandem photovoltaic module, with the effective radius of the affected area continuously increasing approximately with the square root of time, reaching about 23.6 mm after 504 hours, affecting a large number of adjacent cells. In Example 3, the water and oxygen were blocked after reaching the grid walls around the damaged micro-region, and the affected area quickly saturated and stabilized within the physical boundary of the single closed micro-region 13 (approximately 0.75 mm equivalent radius), no longer spreading to adjacent closed micro-regions. Even under the most severe penetrating local damage scenario, Example 3 could still firmly lock the failure affected area within the single closed micro-region 13, while Comparative Example 3 experienced uncontrollable large-area spread. This directly proves the effectiveness and robustness of "local failure blocking (regional water locking)" from a mechanistic perspective.
[0077] Example 4: Preparation of honeycomb water-blocking layer by inkjet printing (low mesh modulus, high adhesive modulus) The fourth embodiment of the method for preparing a four-terminal perovskite-crystalline silicon tandem photovoltaic module of the present invention includes the following steps: Step 41: Pre-fabricate the perovskite top cell 3 and the crystalline silicon bottom cell 6 respectively. The substrate of the perovskite top cell 3 is flexible polyimide, and the width of the metal grid lines on the upper surface of the crystalline silicon bottom cell 6 is 130 μm.
[0078] Step 42: Using inkjet printing combined with a mask, a pre-prepared photocurable coating solution is deposited onto the upper surface of the crystalline silicon bottom cell 6, directly above the metal grid lines, according to a preset pattern. Pre-curing (pre-crosslinking) is then performed to shape the composite water-blocking mesh 4 with multiple closed micro-regions 13. The inkjet printing uses a piezoelectric printhead with a nozzle diameter of 25 μm, a droplet volume of 10 pL, a printing speed of 50 mm / s, and 3 printing layers, with a wet film thickness controlled at 45 μm. After printing, the mesh is pre-baked on an 80°C hot plate for 1 minute to evaporate the solvent. Subsequently, it is cured using a 385 nm UV-LED in a nitrogen atmosphere at an energy of 600 mJ / cm². The elastic modulus of the cured composite water-blocking mesh 4 is approximately 5 MPa. The composite water-blocking mesh 4 is a rectangular mesh with a side spacing of 5 mm. The width of the composite water-blocking mesh 4 is 120 μm, and its height is 20 μm.
[0079] In this embodiment, the components of the photocurable spraying solution are: 75 parts of a first photocurable resin matrix (a mixture of aliphatic polyurethane acrylate and acrylate-modified polybutadiene, with a mass ratio of 1:1), 25 parts of a flexible diluent monomer (laurate acrylate), 15 parts of a flexible block copolymer (polypropylene glycol and diacrylate copolymer), 5 parts of a first photoinitiator (a compound of bis(phosphine oxide) and thioxanthone, with a mass ratio of 4:1), 4 parts of a hydrophobically modified water-absorbing filler (nanoscale zeolite with a surface treated with organosilane hydrophobicity, D50≤200nm), 0.8 parts of a lubricant (BYK-345), and an appropriate amount of a first solvent (propylene glycol methyl ether), adjusted to a final viscosity of 12 cP at 25°C, with a solid content controlled at 30%.
[0080] Step 43: A quantitative amount of optical coupling adhesive 5 with a viscosity of 50 mPa·s is filled into each sealed micro-region 13, ensuring it fills each micro-region 13 and makes tight contact with the sidewalls of the composite water-blocking mesh 4. The vacuum level is controlled at -0.09 MPa to ensure no air bubbles are present during filling. A 365 nm UV-LED surface light source is used to expose the composite water-blocking mesh 4 and optical coupling adhesive 5 from above, with a light intensity of 80 mW / cm² and an exposure time of 80 seconds. This initiates a free radical copolymerization reaction at the interface between the composite water-blocking mesh 4 and the optical coupling adhesive 5, forming a 5 μm thick IPN self-locking interface 10 in situ, resulting in a honeycomb water-blocking layer 7. The elastic modulus of the cured optical coupling adhesive 5 is approximately 200 MPa.
[0081] In this embodiment, the optical coupling adhesive 5 comprises: 40 parts of oligomer (a mixture of bisphenol A epoxy resin and polyurethane acrylate, in a mass ratio of 1:1), 50 parts of curing diluent (a mixture of 3-ethyl-3-hydroxymethyloxetane and isobornyl acrylate, in a mass ratio of 1:1), 5 parts of cationic photoinitiator (triarylthionium salt), 3 parts of free radical photoinitiator (2-hydroxy-2-methyl-1-phenyl-1-propanone), and 1 part of additive (a mixture of γ-glycidyl etheroxypropyltrimethoxysilane and BYK-307 defoamer, in a mass ratio of 1:1).
[0082] Step 44: Sequentially stack the backsheet 9, the lower encapsulating film 8, the crystalline silicon bottom cell 6 with the honeycomb water-blocking layer 7 already prepared on its upper surface, the perovskite top cell 3, the upper encapsulating film 2, and the front cover plate 1 together, and place the entire assembly into a laminator for lamination to complete the fabrication of the four-terminal perovskite-crystalline silicon tandem photovoltaic module. The lamination parameters are: vacuuming for 6 minutes, lamination temperature 140℃, pressure -65kPa, and holding pressure for 18 minutes.
[0083] Example 5: Preparation of a honeycomb water-blocking layer (medium mesh modulus, medium adhesive modulus) by inkjet printing A fifth embodiment of the method for preparing a four-terminal perovskite-crystalline silicon tandem photovoltaic module of the present invention includes the following steps: Step 51: Pre-fabricate the perovskite top cell 3 and the crystalline silicon bottom cell 6 respectively. The substrate of the perovskite top cell 3 is glass, and the width of the metal grid lines on the upper surface of the crystalline silicon bottom cell 6 is 140 μm.
[0084] Step 52: Using inkjet printing combined with a mask, a pre-prepared photocurable spray solution is deposited onto the upper surface of the crystalline silicon bottom cell 6, directly above the metal grid lines, according to a preset pattern. Pre-curing (pre-crosslinking) is then performed to shape the composite water-blocking mesh 4 with multiple closed micro-regions 13. The inkjet printing uses a thermal printhead with a nozzle diameter of 30 μm, a droplet volume of 15 pL, a printing speed of 40 mm / s, and 4 printing layers, with a wet film thickness controlled at 50 μm. After printing, the mesh is pre-baked on a hot plate at 70°C for 1.5 minutes to evaporate the solvent. Subsequently, it is cured using a 395 nm UV-LED in a nitrogen atmosphere at an energy of 900 mJ / cm². The elastic modulus of the cured composite water-blocking mesh 4 is approximately 10 MPa. The composite water-blocking mesh 4 is a regular hexagon with a side-to-side distance of 18 mm. The width of the composite water-blocking mesh 4 is 135 μm, and its height is 35 μm.
[0085] In this embodiment, the components of the photocurable spraying solution are: 80 parts of a first photocurable resin matrix (a mixture of aliphatic polyurethane acrylate and acrylate-modified polybutadiene, with a mass ratio of 1:1), 20 parts of a flexible diluent monomer (isodecyl acrylate), 20 parts of a flexible block copolymer (polypropylene glycol and diacrylate copolymer, with a molecular weight of approximately 2000 Da), 3 parts of a first photoinitiator (a compound of bis(phosphine oxide) and thioxanthone, with a mass ratio of 3:1), 5 parts of a hydrophobically modified water-absorbing filler (organic-inorganic hybrid hygroscopic nanoparticles, sodium polyacrylate-grafted silica), 1 part of a lubricant (nonionic surfactant), and an appropriate amount of a first solvent (dipropylene glycol dimethyl ether), adjusted to a final viscosity of 8 cP at 25°C, with the solid content controlled at 25%.
[0086] Step 53: A quantitative amount of optical coupling adhesive 5 with a viscosity of 275 mPa·s is filled into each sealed micro-region 13, ensuring it fills each micro-region 13 and makes tight contact with the sidewalls of the composite water-blocking mesh 4. The vacuum level is controlled at -0.08 MPa to ensure no air bubbles are present during filling. A 365 nm UV-LED surface light source is used to expose the composite water-blocking mesh 4 and optical coupling adhesive 5 from above at a light intensity of 120 mW / cm² for 50 seconds. This initiates a free radical copolymerization reaction at the interface between the composite water-blocking mesh 4 and the optical coupling adhesive 5, forming an 8 μm thick IPN self-locking interface 10 in situ, resulting in a honeycomb water-blocking layer 7. The elastic modulus of the cured optical coupling adhesive 5 is approximately 150 MPa.
[0087] In this embodiment, the optical coupling adhesive 5 comprises: 50 parts of oligomer (a mixture of bisphenol A type epoxy resin and polyurethane acrylate, in a mass ratio of 2:1), 40 parts of curing diluent (a mixture of 3-ethyl-3-hydroxymethyloxetane and isobornyl acrylate, in a mass ratio of 1:2), 3.5 parts of cationic photoinitiator (triarylthionium salt), 2 parts of free radical photoinitiator (2-hydroxy-2-methyl-1-phenyl-1-propanone), and 0.5 parts of additive (a mixture of γ-glycidyl etheroxypropyltrimethoxysilane and BYK-307 defoamer, in a mass ratio of 1:2).
[0088] Step 54: Sequentially stack the backsheet 9, lower encapsulating film 8, crystalline silicon bottom cell 6 with a pre-prepared honeycomb water-blocking layer 7 on its upper surface, perovskite top cell 3, upper encapsulating film 2, and front cover plate 1 together, and place the entire assembly into a laminator for lamination to complete the fabrication of the four-terminal perovskite-crystalline silicon tandem photovoltaic module. The lamination parameters are: vacuum for 5 minutes, lamination temperature 145℃, pressure -60kPa, and heat and pressure holding for 15 minutes.
[0089] Example 6: Preparation of a honeycomb water-blocking layer (high mesh modulus, low adhesive modulus) by inkjet printing The sixth embodiment of the method for preparing a four-terminal perovskite-crystalline silicon tandem photovoltaic module of the present invention includes the following steps: Step 61: Pre-fabricate the perovskite top cell 3 and the crystalline silicon bottom cell 6 separately. The substrate of the perovskite top cell 3 is flexible polyethylene naphthalate, and the width of the metal grid lines on the upper surface of the crystalline silicon bottom cell 6 is 150 μm.
[0090] Step 62: Using inkjet printing combined with a mask, a pre-prepared photocurable spray solution is deposited onto the upper surface of the crystalline silicon bottom cell 6 directly above the metal grid lines according to a preset pattern. Pre-curing (pre-crosslinking) is then performed to shape the composite water-blocking mesh 4 with multiple closed micro-regions 13. The inkjet printing uses a continuous inkjet printhead with a nozzle diameter of 20 μm, a droplet volume of 8 pL, a printing speed of 60 mm / s, 5 printing layers, and a wet film thickness controlled at 55 μm. After printing, the mesh is pre-baked on a 60°C hot plate for 2 minutes to evaporate the solvent. Subsequently, it is cured using a 405 nm UV-LED in a nitrogen atmosphere at an energy of 1000 mJ / cm². The elastic modulus of the cured composite water-blocking mesh 4 is approximately 15 MPa. The composite water-blocking mesh 4 is a rhomboid mesh with a side-to-side distance of 30 mm. The width of the composite water-blocking mesh 4 is 150 μm, and its height is 50 μm.
[0091] In this embodiment, the components of the photocurable spraying solution are: 70 parts of a first photocurable resin matrix (a mixture of aliphatic polyurethane acrylate and acrylate-modified polybutadiene, with a mass ratio of 1:1), 30 parts of a flexible diluent monomer (a mixture of lauryl acrylate and isodecyl acrylate, with a mass ratio of 1:1), 10 parts of a flexible block copolymer (a copolymer of polypropylene glycol and diacrylate), 6 parts of a first photoinitiator (a compound of bis(phosphine oxide) and thioxanthone, with a mass ratio of 5:1), 3 parts of a hydrophobically modified water-absorbing filler (nanoscale zeolite with a surface treated with organosilane hydrophobicity, D50≤200nm), 0.5 parts of a lubricant (BYK-345), and an appropriate amount of a first solvent (propylene glycol methyl ether), adjusted to a final viscosity of 15 cP at 25°C, with a solid content controlled at 35%.
[0092] Step 63: Quantitatively fill each sealed micro-region 13 with optical coupling adhesive 5 with a viscosity of 500 mPa·s, ensuring it fills each micro-region 13 and makes tight contact with the sidewalls of the composite water-blocking mesh 4. The vacuum level is controlled at -0.07 MPa to ensure bubble-free filling. The composite water-blocking mesh 4 and optical coupling adhesive 5 are exposed from above using a 365 nm UV-LED surface light source with a light intensity of 150 mW / cm² for 40 seconds. This initiates a free radical copolymerization reaction at the interface between the composite water-blocking mesh 4 and the optical coupling adhesive 5, forming a 10 μm thick IPN self-locking interface 10 in situ, resulting in the honeycomb water-blocking layer 7. The elastic modulus of the cured optical coupling adhesive 5 is approximately 100 MPa.
[0093] In this embodiment, the optical coupling adhesive 5 comprises: 60 parts of oligomer (a mixture of bisphenol A epoxy resin and polyurethane acrylate, in a mass ratio of 1:2), 30 parts of curing diluent (a mixture of 3-ethyl-3-hydroxymethyloxetane and isoborneol acrylate, in a mass ratio of 2:1), 2 parts of cationic photoinitiator (triarylthionium salt), 1 part of free radical photoinitiator (2-hydroxy-2-methyl-1-phenyl-1-propanone), and 0.1 parts of additive (a mixture of γ-glycidyl etheroxypropyltrimethoxysilane and BYK-307 defoamer, in a mass ratio of 2:1).
[0094] Step 64: Sequentially stack the backsheet 9, the lower encapsulating film 8, the crystalline silicon bottom cell 6 with the honeycomb water-blocking layer 7 already prepared on its upper surface, the perovskite top cell 3, the upper encapsulating film 2, and the front cover plate 1 together, and place the entire assembly into a laminator for lamination to complete the fabrication of the four-terminal perovskite-crystalline silicon tandem photovoltaic module. The lamination parameters are: vacuuming for 4 minutes, lamination temperature 150℃, pressure -55kPa, and holding pressure for 12 minutes.
[0095] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A four-terminal perovskite-crystalline silicon tandem photovoltaic module, comprising a front cover plate (1), an upper encapsulating film (2), a perovskite top cell (3), a crystalline silicon bottom cell (6), a lower encapsulating film (8), and a back sheet (9) stacked together, characterized in that, A honeycomb water-blocking layer (7) is provided between the perovskite top cell (3) and the crystalline silicon bottom cell (6). The honeycomb water-blocking layer (7) includes a composite water-blocking grid (4) and an optical coupling adhesive (5). The composite water-blocking grid (4) divides the entire effective power generation area (12) into multiple isolated closed micro-regions (13). The optical coupling adhesive (5) is filled in each closed micro-region (13). A free radical copolymerization reaction is initiated at the interface between the composite water-blocking grid (4) and the optical coupling adhesive (5) to form an IPN self-locking interface (10) in situ. The elastic modulus of the composite water-blocking grid (4) is 5~15MPa, and the elastic modulus of the optical coupling adhesive (5) is 100~200MPa. The IPN self-locking interface (10) forms a water-blocking boundary physically, and locks the composite water-blocking grid (4) and the optical coupling adhesive (5) together at the molecular level.
2. The four-terminal perovskite-crystalline silicon tandem photovoltaic module as described in claim 1, characterized in that, The material used to prepare the composite water-blocking mesh (4) is a photocurable spraying solution. The photocurable spraying solution consists of 70-80 parts of a first photocurable resin matrix, 20-30 parts of a flexible diluent monomer, 10-20 parts of a flexible block copolymer, 3-6 parts of a first photoinitiator, 3-5 parts of a hydrophobic modified water-absorbing filler, 0.5-1 parts of a lubricant, and an appropriate amount of a first solvent. The final viscosity of the photocurable spraying solution is 8-15 cP at 25°C, and the solid content is controlled at 25-35%. The first photocurable resin matrix is an aliphatic polyurethane acrylate and... The mixture comprises acrylate-modified polybutadiene in a mass ratio of 1:1; the flexible diluent monomer is lauryl acrylate or isodecyl acrylate; the flexible block copolymer is a copolymer of polypropylene glycol and diacrylate; the first photoinitiator is bis(phosphine oxide) compounded with thioxanthones in a mass ratio of 3:1 to 5:1; the hydrophobically modified absorbent filler is nanoscale zeolite or organic-inorganic hybrid hygroscopic nanoparticles with a surface treated with organosilane hydrophobicity; the lubricant is a nonionic surfactant; and the first solvent is propylene glycol methyl ether or dipropylene glycol dimethyl ether.
3. The four-terminal perovskite-crystalline silicon tandem photovoltaic module as described in claim 1, characterized in that, The material used to prepare the composite water-blocking mesh (4) is a photocurable coating solution. The photocurable coating solution consists of 60-70 parts of a second photocurable resin matrix, 15-25 parts of a flexible block copolymer, 10-20 parts of an active diluent, 2-4 parts of a second photoinitiator, 3-8 parts of a moisture-absorbing filler, 0.5-1 parts of a leveling agent, 0.5-2 parts of a thixotropic agent, and an appropriate amount of a second solvent. The coating viscosity of the photocurable coating solution is 1000-6000 cP at 25°C, and the solid content is controlled at 20-30%. The second photocurable resin matrix is a mixture of bisphenol A type epoxy acrylate and polybutadiene modified olefin resin, with a mass mixing ratio of 3:
2. The flexible block copolymer... The components are: a copolymer of polypropylene glycol and diacrylate or a copolymer of polytetrahydrofuran ether and diacrylate; an active diluent is a mixture of isobornyl acrylate and trimethylolpropane triacrylate in a mass ratio of 3:1 to 5:1; a second photoinitiator is a composition of 2-hydroxy-2-methyl-1-phenyl-1-propanone and diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide in a mass ratio of 1:2 to 2:1; a moisture-absorbing filler is nano-sized zeolite with a surface treated with organosilane hydrophobicity; a leveling agent is BYK-333; a thixotropic agent is organobentonite or a polyurea compound; and a second solvent is a mixture of cyclohexanone and propylene glycol methyl ether acetate in a mass ratio of 1:
1.
4. The four-terminal perovskite-crystalline silicon tandem photovoltaic module as described in claim 1, characterized in that, The material used to prepare the optical coupling adhesive (5) consists of 40-60 parts of oligomer, 30-50 parts of curing diluent, 2-5 parts of cationic photoinitiator, 1-3 parts of free radical photoinitiator, and 0.1-1 parts of additives. The viscosity of the optical coupling adhesive (5) before curing is 50-500 mPa·s, and the refractive index after curing is 1.50-1.
53. The oligomer is a mixture of bisphenol A epoxy resin and polyurethane acrylate. The curing diluent is 3-ethyl-3-hydroxymethyloxetane as a cationic curing diluent, combined with isoborneol acrylate as a free radical curing diluent. The cationic photoinitiator is triarylsulfonium salt. The free radical photoinitiator is 2-hydroxy-2-methyl-1-phenyl-1-propanone. The additives are γ-glycidyl etheroxypropyltrimethoxysilane silane coupling agent and BYK-307 defoamer.
5. The four-terminal perovskite-crystalline silicon tandem photovoltaic module as described in claim 1, characterized in that, The shape of the closed micro-region (13) is any one of rectangle, rhombus, regular hexagon or other polygon, and the distance between opposite sides of the closed micro-region (13) is 5~30mm.
6. The four-terminal perovskite-crystalline silicon tandem photovoltaic module as described in claim 1, characterized in that, The height of the honeycomb water-blocking layer (7) is 20~50μm, and the wall thickness of the composite water-blocking grid (4) is 120~150μm.
7. A method for preparing a four-terminal perovskite-crystalline silicon tandem photovoltaic module as described in any one of claims 2, 4 to 6, characterized in that, Includes the following steps: Step 1: Pre-fabricate perovskite top cell (3) and crystalline silicon bottom cell (6) respectively. Step 2: Using inkjet printing combined with a mask, the pre-prepared curing spray solution is deposited on the upper surface of the crystalline silicon bottom cell (6) according to the preset pattern, and then pre-cured to shape it, resulting in a composite water-blocking grid (4) with multiple closed micro-regions (13). Step 3: Quantitatively fill each closed micro-region (13) with optical coupling adhesive (5), and use a UV-LED surface light source to expose the composite water-blocking grid (4) and optical coupling adhesive (5) from above, so that a free radical copolymerization reaction is initiated at the interface between the composite water-blocking grid (4) and the optical coupling adhesive (5), forming an in-situ IPN self-locking interface (10) to obtain a honeycomb water-blocking layer (7). Step 4: Stack the backplate (9), the lower encapsulation film (8), the crystalline silicon bottom cell (6) with the honeycomb water-blocking layer (7) already prepared on the upper surface, the perovskite top cell (3), the upper encapsulation film (2), and the front cover plate (1) together in sequence, and put the whole assembly into a laminator for lamination to complete the preparation of the four-terminal perovskite-crystalline silicon tandem photovoltaic module.
8. The method for preparing a four-terminal perovskite-crystalline silicon tandem photovoltaic module as described in claim 7, characterized in that, In step two, the curing spray solution is prepared in advance using the following method: at room temperature, the first photocurable resin matrix, flexible diluent monomer, flexible block copolymer, lubricant and appropriate amount of first solvent are mixed evenly, the first photoinitiator is added under light-protected conditions, and the mixture is stirred until completely dissolved. The hydrophobic modified water-absorbing filler is slowly added, and ultrasonic dispersion is performed to ensure no agglomeration. Finally, a PTFE filter membrane is used for terminal filtration, and the filtered photocurable spray solution is stored in a light-protected ink can for later use.
9. A method for preparing a four-terminal perovskite-crystalline silicon tandem photovoltaic module as described in any one of claims 3 to 6, characterized in that, Includes the following steps: Step 1: Pre-fabricate perovskite top cell (3) and crystalline silicon bottom cell (6) respectively. Step 2: Using a slit extrusion coating combined with a mask, the pre-prepared curing coating solution is deposited on the upper surface of the crystalline silicon bottom cell (6) according to a preset pattern, and then pre-cured to shape it, resulting in a composite water-blocking mesh (4) with multiple closed micro-regions (13). Step 3: Quantitatively fill each closed micro-region (13) with optical coupling adhesive (5), and use a UV-LED surface light source to expose the composite water-blocking grid (4) and optical coupling adhesive (5) from above, so that a free radical copolymerization reaction is initiated at the interface between the composite water-blocking grid (4) and the optical coupling adhesive (5), forming an in-situ IPN self-locking interface (10) to obtain a honeycomb water-blocking layer (7). Step 4: Stack the backplate (9), the lower encapsulation film (8), the crystalline silicon bottom cell (6) with the honeycomb water-blocking layer (7) already prepared on the upper surface, the perovskite top cell (3), the upper encapsulation film (2), and the front cover plate (1) together in sequence, and put the whole assembly into a laminator for lamination to complete the preparation of the four-terminal perovskite-crystalline silicon tandem photovoltaic module.
10. The method for preparing a four-terminal perovskite-crystalline silicon tandem photovoltaic module as described in claim 9, characterized in that, In step 2, the curing spray solution is prepared in advance using the following method: the second photocurable resin matrix, flexible block copolymer, and reactive diluent are dissolved in the second solvent and heated and stirred in a 50°C water bath until completely dissolved; after cooling the obtained solution to room temperature, the second photoinitiator, leveling agent, and thixotropic agent are added under light-protected conditions and stirred for 30 minutes; then the moisture-absorbing filler is slowly added and dispersed at high speed for 45 minutes; the solution is filtered and degassed using a 10~20μm filter membrane, and the obtained curing spray solution is allowed to stand and mature for 12 hours before use.
Citation Information
Patent Citations
Method for in situ tailoring the metallic component of ceramic articles and articles made thereby
IE61215B1
Perovskite / crystalline silicon laminated solar cell and preparation method thereof
CN120076566A
KR20260072550A
